DFT insights into the Ni-catalyzed regioselective hydrocarboxylation of unsaturated alkenes with CO2. Issue 42 (5th October 2021) - Shao, Yifan; Nie, Wan; Yao, Chengyu; Ye, Lina; Yu, Haizhu
Abstract : The substituted benzylic group promotes the β-H transfer and subsequent α-carboxylation for aromatic olefins, while β-carboxylation is predominant for aliphatic alkenes due to the disfavored H-transfer (lower proton affinity of aliphatic alkenes). Abstract : The nickel-catalyzed hydrocarboxylation of alkenes using carbon dioxide has recently become an appealing method to prepare functionalized carboxylic acids with high efficiency and regioselectivity. Herein, density functional theory (DFT) calculations were conducted on the Ni-catalyzed hydrocarboxylation of aryl-/alkyl-substituted alkenes with CO2 . The α- and β-carboxylation of aromatic and aliphatic olefins originate from distinct catalytic cycles: H-transfer–carboxylation and carboxylation–H-transfer pathways. The typical hydrometallation–carboxylation mechanism is unlikely because water/carbonic acid (H-resource) are inferior hydride donors.